2023
DOI: 10.3389/fmed.2023.1257589
|View full text |Cite
|
Sign up to set email alerts
|

Transition to remote/hybrid learning during the COVID-19 pandemic among Saudi students of the College of Applied Medical Sciences: a cross-sectional study

Khalid M. Alshamrani,
Enas M. Ghulam,
Maryam Alattas
et al.

Abstract: BackgroundThe novel Coronavirus Disease 2019 (COVID-19) pandemic has presented unparalleled and unique stressors and challenges to the field of applied health sciences education. This study explored how the College of Applied Medical Sciences (COAMS) Saudi students perceive the transition to remote/ hybrid learning during the COVID-19 pandemic.MethodsA cross-sectional exploratory investigation was carried out during the months of February and March in the year 2023 among 196- COAMS Saudi students, using the 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…A study conducted revealed positive attitude towards IPE among pharmacy academics, with a majority recognizing the importance of IPE. 17 Through the inclusion of IPE in courses, both staff members and students reported having a better awareness of team responsibilities and communication. These findings also support the study of Rodger et al (2010), which found that healthcare workers had favorable opinions of IPE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted revealed positive attitude towards IPE among pharmacy academics, with a majority recognizing the importance of IPE. 17 Through the inclusion of IPE in courses, both staff members and students reported having a better awareness of team responsibilities and communication. These findings also support the study of Rodger et al (2010), which found that healthcare workers had favorable opinions of IPE.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recognizing that IPE interactions provide aspiring health professionals invaluable practice and help them develop the attitudes and skills necessary for future interprofessional cooperation, the infusion of IPE into professional health sciences programs has proliferated. 17 However, since much of professional healthcare programs develop their student body via clinical engagement with the mentorship of clinical preceptors, understanding the attitudes and perceptions of clinical preceptors towards IPE and their overall readiness to engage in interprofessional care is imperative. Clinical preceptors function as role models, knowledge https://doi.org/10.2147/AMEP.S451938…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, during the year of 2018–2019, three research articles were published ( 52 54 ), followed by a lack of publications in 2020. Yet, in 2021, there was a considerable rise with seven research publications ( 55 61 ), and it continued to grow with 10 research publications in 2022–2023 ( 62 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…The temporary closure of education institutions displaced 1.6 billion students from in-person instruction, including 220 million from higher education institutions (HEIs) (Farnell et al, 2021;UNESCO, 2021). This sudden shift not only tested the resilience of educational infrastructures but also challenged the pedagogical, technological, and psychological preparedness of institutions and individuals (Alshamrani et al, 2023;Mushtaha et al, 2022).…”
mentioning
confidence: 99%